Ripening and quality of ’Laetitia’ plums following harvest and cold storage as affected by inhibition of ethylene action - Argenta, Luiz Carlos; Krammes, Juliana Golin; Megguer, Clarice Aparecida; Amarante, Cassandro Vidal Talamini; Mattheis, James (Pesquisa Agropecuaria Brasileira, 2003)
The inhibition of ethylene action by 1-methylcyclopropene (1-MCP) extends shelf and storage life of many climacteric fruits. However, 1-MCP appears to have limited effects on stone fruit depending on specie and cultivar. The effects of 1-MCP on ripening and quality of 'Laetitia' plums were determined during ripening at 23oC following harvest and cold storage. Japanese plums (Prunus salicina, cv. Laetitia) were harvested at mature pre-climacteric stage, cooled to 2oC within 36 hours of harvest and then treated with 0, 0.05, 0.10, 0.50 or 1.00 mL L-1 of 1-MCP at 1°C for 24 hours. Following treatment, fruits were either held at 23oC for 16 days or stored at 1oC for 50 days. Fruits were removed from cold storage at 10-day intervals and allowed to ripe at 23°C for five days. A delay of climacteric respiration and ethylene production by 1-MCP treatment during ripening following harvest and cold storage was associated to a slow rate of fruit softening. 1-MCP treatment also delayed the loss of titratable acidity and changes of flesh and skin color, whereas it had little or no effect on soluble solids content. 1-MCP effects were concentration- and storage duration-dependent and, generally, a saturation fruit response to 1-MCP occurred between 0.5 and 1.0 mL L-1. During ripening, 1-MCP treated fruits attained quality similar to that of controls. Results indicated that 1-MCP treatment may extend shelf life (23oC) and storage life (1oC) of 'Laetitia' plums by approximately six and 20 days, respectively.